NETWORK MODELS OF INSTITUTIONALIZATION IN EDUCATION FOR THE KNOWLEDGE SOCIETY (BY THE EXAMPLE OF "THE STEP INTO THE FUTURE" PROGRAMME) - Alexander O. Karpov (Высшее образование в России)
The concept of knowledge society is an influential paradigm that defines the processes of modernization in education sphere. The development of integrated and network systems is becoming a genetic feature of the educational institution of the research type, and the study of their opportunities and configurations provides the key to effective forms of modern education organization. The paper presents the results of the theoretical study on the problem of institutionalization of the up-to-date model of research education that describes the structure of learning communities, the forms of their social realization and systemic genesis.